Gostota napak in odpovedi - problematično merilo kakovosti - Dogša, Tomaž (Uporabna informatika (Ljubljana), 1998)
In the paper we investigate the problems of collecting and interpreting the fault and failure densisties. Both measures are used as an indicator of product (reliability) and proces quality. Metrics have so far not been sufficiently developed. Thus, results obtained from them can be very inaccurate. This drawback must be considered when we would like to interpret the results of comparative analyses. We also describe the reasons for inaccuracy of foult and failure densisties. A suitable nomenclature needed for writing problem reports is also proposed.
Keywords: kvaliteta; merjenje; napake; programska oprema